2020
DOI: 10.3390/molecules25092130
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Immunomodulatory Activities of a Novel Water-Soluble Derivative of Ellipticine

Abstract: Cancer still remains a major public health concern around the world and the search for new potential antitumor molecules is essential for fighting the disease. This study evaluated the anticancer and immunomodulatory potential of the newly synthetized ellipticine derivate: sodium bromo-5,11-dimethyl-6H-pyrido[4,3-b]carbazole-7-sulfonate (Br-Ell-SO3Na). It was prepared by the chlorosulfonation of 9-bromoellipticine. The ellipticine-7-sulfonic acid itself is not soluble, but its saponification with sodium hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Hopefully, this study could be used as the basis for both in-vivo and in-vitro studies, hence new herbal plant-based therapies can be found for treating melanoma. Ochrosia vieillardii, Ochrosia acuminata, Ochrosia moorei, Strychnos dinkagei, and families of Apocynaceae 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, this study could be used as the basis for both in-vivo and in-vitro studies, hence new herbal plant-based therapies can be found for treating melanoma. Ochrosia vieillardii, Ochrosia acuminata, Ochrosia moorei, Strychnos dinkagei, and families of Apocynaceae 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using electron microscopy, the authors showed further ultrastructure changes due to apoptosis activation by EPED3 on MM cells, such as the destruction of mitochondrial inner cristae, nuclear pyknosis, and formation of multiple cytosolic vacuoles, hoping for its use in vivo as an antimyeloma agent in combination with conventional drugs [ 62 ]. However, in vitro studies are still ongoing regarding the identification of other effective water-soluble derivatives of Ellipticine, such as anticancer agents and immunomodulators for its low bioavailability [ 63 ].…”
Section: Re-sensitization To Chemotherapy Through Caspase-dependenmentioning
confidence: 99%
“…6,14−17 The advances in the chemical modification of natural products have highly motivated the discovery and development of new pesticides or pharmaceuticals. 18−23 In particular, chemically modified carbazole derivatives augment biological silhouettes and display antimicrobial, 24,25 anticancer, 26,27 antiinflammatory, 28,29 antiproliferative, 30,31 antituberculosis, 32,33 and anti-Alzheimer effects. 34,35 Because of the distinctive electronic and charge-transport performance of this privileged carbazole skeleton, the molecular design and engineering based on this scaffold and the underlying mechanism of action were continuously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The advances in the chemical modification of natural products have highly motivated the discovery and development of new pesticides or pharmaceuticals. In particular, chemically modified carbazole derivatives augment biological silhouettes and display antimicrobial, , anticancer, , anti-inflammatory, , antiproliferative, , antituberculosis, , and anti-Alzheimer effects. , Because of the distinctive electronic and charge-transport performance of this privileged carbazole skeleton, the molecular design and engineering based on this scaffold and the underlying mechanism of action were continuously investigated. , In our previous work, we developed a type of 9-substituted carbazole derivative bearing an isopropanolamine linker as an antibacterial compound against plant pathogens. We found that the rational modification of the carbazole nucleus can arouse and advance the discovery of more effective ingredients that can be used in the control of bacterial diseases .…”
Section: Introductionmentioning
confidence: 99%